2022
DOI: 10.1177/01945998221117095
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomics in Otolaryngologic Surgery: A State of the Art Review

Abstract: Objective Otolaryngology is a surgical field with a high degree of ergonomic risk. The use of head-mounted lighting, loupe magnification, endoscopes, and microscopes is inherent to the field, coupled with repetitive fine motor movements in a constrained anatomic field as well as static, ergonomically unfavorable postures. We seek to review the otolaryngologic literature on ergonomics, including prevalence, severity, and interventions in decreasing work-related musculoskeletal pain. Data Sources Data were deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 48 publications
0
11
0
2
Order By: Relevance
“…The surgical workplace has been slow to create easily adopted methods to quantify and mitigate ergonomic risk, perhaps due to a lack of awareness and formal training of ergonomic principles during residency . In this way, deliberate training and education in ergonomics is critical for protecting the workforce.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The surgical workplace has been slow to create easily adopted methods to quantify and mitigate ergonomic risk, perhaps due to a lack of awareness and formal training of ergonomic principles during residency . In this way, deliberate training and education in ergonomics is critical for protecting the workforce.…”
Section: Discussionmentioning
confidence: 99%
“…Ergonomic interventions in plastic surgery have been associated with fewer errors and self-reported decreased muscular fatigue by taking 20-second breaks to rest muscles every 20 minutes throughout the procedure . Other interventions have included changing patient positioning, surgeon positioning, and novel instruments or support devices . Furthermore, surgeons who exercise regularly (>5 hours per week or >3 days per week) have reduced symptoms of musculoskeletal disorders .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ese approaches are time-bound and might distort the holistic picture of the development of the given topic (for some strong recent examples of medicinerelated state-of-the-art review, see [34,35]).…”
Section: State-of-the-art Reviewmentioning
confidence: 99%
“…7,8 A recent review examined surgical ergonomics in otolaryngology, and found a high prevalence of work-related musculoskeletal disorders. 9 Importantly, the authors identified multiple studies that found effective ergonomic interventions, including the use of novel equipment and instrumentation. Despite this, the use of more ergonomic devices and equipment has not been widely adopted in our field.…”
mentioning
confidence: 99%